Pengembangan Game Spelling Word Scrabble Untuk Perkembangan Aspek Bahasa Pada Anak Usia Dini Usia 5-6 Tahun - Shofrotul Faizah; Siti Masitoh (Universitas PGRI Semarang, 2023)
AbstractThis research is motivated by the results of an analysis which shows that media for early childhood 5-6 years is needed for the development of aspects of language development. This research aims to develop a media that is suitable for the characteristics of early childhood 5-6 years. The method used is Research and Development (R&D) research. The subjects used in this study were 15 children aged 5-6 years from an educational institution in Sukodono, Sidoarjo. The results of this study are, as follows. 1) Media spelling word scrabble to develop aspects of language development in early childhood 5-6 years is developed based on the steps in DDD-E, namely Decide, Design, Development and Evaluate. 2) The effectiveness of the spelling word scrabble media product is